RESTRUKTURISASI MAJELIS PERMUSYAWARATAN RAKYAT SESUDAH AMANDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Alsidik Syahputra; Dodi Haryono; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Institution of the People's Consultative Assembly was referred to as the supreme perpetrators of popular sovereignty even in Article 1 (2) of the Constitution of 1945 before the change formulated by the sentence: